Unraveling the volatile metabolites and potential plant-stimulating properties of organically extracted Caulerpa racemosa - Lalruatfeli, Pachuau; Krishnan, Ramanujam; Janaki, Ponnusamy; Suganthy, Mariappan; Djanaguiraman, Maduraimuthu; Kalpana, Rengabashayam (Frontiers in Sustainable Food Systems, 2024)
Seaweed is an increasingly recognized source of secondary metabolites with a significant role as a plant biostimulant. With the rising popularity of organic farming, there is a pressing need to investigate the utilization of organic solvents derived from natural sources for seaweed extraction. Understanding the composition of these extracts is crucial for elucidating their role as biostimulants in plant growth. Hence, the present study aimed to explore the phytochemical composition and untargeted metabolomics of four extracts of Caulerpa racemosa (SW), prepared organically using vinegar, fermented buttermilk, and cow urine, in comparison with the conventionally used solvent, water. Approximately 95 volatile metabolites that belong to 22 chemical classes were identified through GC–MS analysis. The major classes detected include benzene and its substituted derivatives (24%), fatty acyls (17%), phenols (12%), benzofurans (8%), organo-oxygen compounds (6%), steroids and steroid derivatives (5%), and indole and its derivatives (4%). A significant shift in the composition of volatile metabolites was observed among the organic extracts as determined through a combination of various statistical analyses. A principal component analysis (PCA) highlighted seven principal components (PCs), which accounted for 99.9% of the total variance. Hierarchical cluster analysis delineated two distinct clusters, which signify a clear differentiation among the organic extracts. Furthermore, partial least squares discriminant analysis (PLS-DA) highlighted 49 volatile metabolites of significant importance, evident from variable importance in projection (VIP) scores of more than 1. These results underscore the intricate and distinct metabolomes inherent in Caulerpa racemosa organic extracts, hinting at their potential as biostimulants for plant growth. This study establishes a foundation for deeper investigations into seaweed extraction utilizing easily accessible organic solvents, presenting potential benefits for farmers.